Imitation Modeling of an Inter-Turn Short Circuit of an Asynchronous Motor Stator Winding for Diagnostics of Auxiliary Electric Drives of Transport Infrastructure - Sergey Goolak; Juraj Gerlici; Oleg Gubarevych; Tomáš Lack; Mikhail Pustovetov (Communications - Scientific letters of the University of Zilina, 2021)
A scientific approach to calculating the parameters and characteristics of an asynchronous motor in the inter-turn short circuit mode in one phase of the stator is proposed to create the foundations of a diagnostic complex for assessing the condition of asynchronous motors of the transport infrastructure. This approach consists of the fact that in the model with which the research is carried out, it is proposed to take into account changes in the mutual inductance of the motor when the AC impedance of one of the stator phases changes. Using a new approach to modeling processes occurring in an asynchronous motor during the inter-turn short circuit in one phase of the stator, pulsations of the torque on the motor shaft were studied for different values of the AC impedance and resistance of one of the stator winding phases, which corresponds to varying degrees of the inter-turn short circuits.